Trends and focuses of hantavirus researches: a global bibliometric analysis and visualization from 1980 to 2020 - Xiao Wei; Xinlou Li; Shuxuan Song; Xiaohui Wen; Tiezhi Jin; Chenxi Zhao; Xubin Wu; Kun Liu; Zhongjun Shao (BMC, 2022)
Abstract Background There have been worldwide changes in the researches on hantaviruses in the past several decades. Nevertheless, there are few bibliometric analysis studies this field. We aim to evaluate and visualize the research focuses and trends of this field using a bibliometric analysis way to help understand the developmet and future hotspots of this field. Material and methods Publications related to hantavirus studies were culled from the Web of Science Core Collection to generate trend analysis. The articles and reviews were re-extracted and Countries, institutions, authors, references and keywords in this field were visually analyzed by using VOSviewer and CiteSpace. Results A total of 4408 studies were included and the number of publications regarding hantaviruses significantly increased yearly. Three thousand seven hundred sixteen research articles and reviews were retrieved to generate bibliometric analysis. These studies mainly come from 125 countries led by USA and China and 3312 institutions led by the University of Helsinki. Twelve thousand five hundred twenty nine authors were identified and Vaheri A were the most influential author. Journal of Virology was the journal with the most studies and citations. After analysis, Hemorrhagic fever with renal syndrome, Hantavirus cardiopulmonary syndrome, nephropathia epidemica and related genotypes, clinical symptoms and rodents were the most common keywords and developing areas. Conclusion Research on hantavirus is flourishing. Cooperation among different countries and institutions in this field must be strengthened in the future. The ecology and clinical symptoms of new genotypes, the vaccine development and factors that affect host population distribution and density are current and developing areas of study.